Mating frequency and colony genetic structure analyses reveal unexpected polygyny in the Mediterranean acrobat ant Crematogaster scutellaris. Issue 2 (3rd March 2020) - Masoni, Alberto; Frizzi, Filippo; Natali, Chiara; Ciofi, Claudio; Santini, Giacomo
Abstract : Among eusocial Hymenoptera, ants represent an unrivalled example of diversity in number of queens and mating systems. Ant colonies may have one (monogyny) or several queens (polygyny) which can mate once (monoandry) or several times (polyandry). In this study, we analysed the genetic structure and breeding system of the Mediterranean acrobat ant Crematogaster scutellaris . Despite its widespread distribution and pivotal role in regulating arthropod communities, many details of the biology of this species have yet to be fully investigated. According to previous studies based on few observations, C. scutellaris is monogynous and monandrous with a claustral foundation phase. We assessed the mating frequency and the number of queens in 40 colonies using highly polymorphic, species-specific nuclear DNA microsatellite loci. The number of queens in each colony was directly inferred from the relatedness of workers. Moreover, in order to determine the proportion of multiple matings by queens, we performed both parental reconstruction analysis using offspring data and direct analysis of the sperm stored in the queen's spermathecae. We investigated relatedness between queens and their mated males. The results showed that, although the majority of the colonies were monogynous, polygyny occurred in 10% of the nests. Monoandry was the norm: we found evidence of multiple paternity in just two out of 40 colonies. Finally, no relatedness was found between queens and their mates, indicating that the latter were from different colonies. This work is the first description of the genetic structure of the colonies of C. scutellaris and provides new insight for further investigation on the social organization, behaviour and ecology of Mediterranean acrobat ants.